Analysis of Biaxial Mechanical Properties and Failure Criterion of Self-Compacting Concrete - Zhang, Jun; Li, Chen; Zhu, Congxiang; Zhao, Zhiqing (Frontiers in Materials, 2021)
Biaxial compression-compression, biaxial tension-compression and compression-shear tests were carried out on self-compacting concrete (SCC) using the rock true triaxial machine and compression-shear hydraulic servo machine to explore the biaxial mechanical properties of SCC. The failure modes and stress-strain curves of SCC under different loading conditions were obtained through experiment. Based on the comparison with the biaxial loading test data of ordinary concrete, the following conclusions are drawn: the failure modes and failure mechanisms under biaxial compression-compression and biaxial tension-compression are similar between SCC and ordinary concrete. Under compression-shear loading, the oblique cracks formed on the lateral surface of the specimen parallel to the shear direction gradually increased and the friction marks on the shear failure section were gradually deepened with the increase of axial compression ratio. The development trend of the stress-strain curve in the principal stress direction was not related to the lateral stress. Under the influence of lateral compressive stress, the principal compressive stress of SCC was increased by 55.78% on average; under biaxial tension-compression, the principal tensile stress of SCC had a maximum reduction of 62.79%; and under the compression-shear action, the shear stress of SCC had a maximum increase of 3.35 times. Compared with the biaxial stress test data of ordinary concrete, it can be seen that the lateral compressive stress had a more significant effect on the principal stress of SCC under biaxial loading. Subsequently, the strength criterion equations of SCC under biaxial loading were proposed based on the principal stress space and octahedral space stress respectively, which have shown good applicability in practice.